ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL TEKS CERPEN BERBASIS KEARIFAN LOKAL SUMATERA SELATAN - Sholihah, Anisau Fitriyatus (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2024)
This research aims to determine the needs analysis for developing e-moduls for short story texts based on local wisdom. The research method uses a survey. Sources of research data were class X students of SMA Negeri 1 Lempuing Jaya and 2 teachers. Data collection techniques using questionnaires and interviews. Questionnaire data analysis used a Likert scale and interviews used descriptive. The results showed that the analysis of needs for e-module development in terms of needs, deficiencies, and desires. In terms of needs, students' mastery of writing short stories is quite good. Teaching materials that only use textbooks and do not provide adequate explanations and evaluations and the density of the material results in a lack of time for needs analysis in terms of deficiencies. The desire to have digital teaching materials that are complete and based on local wisdom Key words: need assesment, e-modul, .local wisdom